Stan i kierunki rozwoju sektora mleczarskiego w regionie małopolskim - Cieślik, Jerzy (Current State and Directions of Dairy Sector Development in the Małopolska Region, 2005)
Current state and directions of dairy sector in the Małopolska region have been presented. In the field of raw material production concentration should be achieved through dynamic restructuring of raw material base focused on specialist dairy farms and concentration of production in the south of the region. The concentration of production and specialization in manufacturing products which are characteristic for the region should be the main directions of its development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 97-101